ELECTROPOLYMERIZATION OF PYRROLE ON COPPER AND HIS EVALUATION AS INHIBITOR IN THE PROCESSES OF CORROSION - La Rosa-Toro Gómez, Adolfo (2022)
In this work, the electrochemical synthesis of the polypyrrole (Ppy) on passivated copper in different media for the study of the anticorrosive properties. These media: 0,3 mol L-1 oxalic acid, phosphate buffer at a concentration of 0,10 mol L-1 dihydrogen phosphate and 0,10 mol L-1 hydrogen phosphate and 0,25 mol L-1 sodium acetate covering a pH range of 1, 4 and 8 respectively. The electropolymerization process of pyrrole occurs in the potentials corresponding to the formation of Ppy, resulting in the adherence of a black material on them (Polypyrrole), characterized by Raman spectroscopy, a technique that informs us of the characteristic peaks of this material in our polymer, the main ones being obtained at 1540 cm-1 corresponding to the vibration of the carbon-carbon double bond in the polymer chain and the one corresponding to the Ppy+ at 1310 cm-1. Finally the studies of the anticorrosive activity by Tafel slopes results in an optimum value of 0,004 mm/year of corrosion rate for polypyrrole film electrodeposited by 40 cycles in oxalic acid against the corrosion rate of metallic copper of 0,907 mm/year.